2008
DOI: 10.1007/s11250-008-9136-3
|View full text |Cite
|
Sign up to set email alerts
|

Participatory investigation of Contagious Caprine Pleuropneumonia (CCPP) in goats in the Hammer and Benna-Tsemay districts of southern Ethiopia

Abstract: The study was conducted in two selected districts of Southern Omo zones of Ethiopia, namely Hammer and Benna-Tsemay, during November 2004 and May 2005 to determine the status of contagious caprine pleuropneumonia (CCPP). Participatory disease investigation was conducted in the goat flocks owned by pastoralists of the districts. Participatory methods such as proportionate piling and matrix scoring of diseases were used to characterise major diseases of goats. Clinical and post-mortem examinations and isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
(14 reference statements)
6
6
2
Order By: Relevance
“…The seasonal pattern of CCPP identified by farmers during onset of rains agreed with previous reports from Southern Ethiopia [11]. This also affirmed previous reports that seasonal calendars were important tool in designing disease control programs [13] [14] and this could be equally targeted as best time for control of CCPP in Agago and Otuke districts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The seasonal pattern of CCPP identified by farmers during onset of rains agreed with previous reports from Southern Ethiopia [11]. This also affirmed previous reports that seasonal calendars were important tool in designing disease control programs [13] [14] and this could be equally targeted as best time for control of CCPP in Agago and Otuke districts.…”
Section: Discussionsupporting
confidence: 89%
“…The present study estimated the overall sero-prevelance of CCPP at 20.8%. This is close to what has been reported (15% -18%) in southern Ethiopia [4] [11]. Our finding was at variance with reports of studies done in Ethiopia [17] [18] and in Beetal goats in Pakistan Hussain, 2012 #51 as well as in East Turkey [19] who documented higher sero-prevalence between 31% and 38%.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The overall prevalence of CCPP in the present study was higher than some of previous studies which were conducted in Southern part of Ethiopia. A relatively lower seroprevalence of 18.61% in South Omo and Arbaminch areas (Mekuria and Asmare, 2010), 15.5% in Hammer and Benna-Tsemay (Mekuria et al, 2008), 20.12% in Borana pastoral area (Gelagay et al, 2007) and 13.2% in Borana and Guji lowlands (Bekele et al, 2011) had been reported. Moreover, Eshete (2006) had also reported seroprevalence of 19.19% using cELISA in Afar pastoral area.…”
Section: Discussionmentioning
confidence: 96%
“…Of these, diseases are widespread with significant impact on the performance of animals (Woldemeskel et al 2002;Tibbo et al 2003;Mekuria et al 2008). For the intervention of such disease problems either by treatment, control or prevention, proper disease diagnosis is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%